Four Instruments to Strengthen Financial Integration in Sub-Saharan Africa - Amadou Sy (Fondation pour les études et recherches sur le développement international (FERDI), 2014)
This paper proposes four tools to strengthen financial integration in sub-Saharan Africa. The first tool, "political commitment devices" can ensure steady progress on the road to an economic community. For instance, stronger regional institutions can monitor progress towards integration and encourage policymakers to respect their regional commitments. Second, the economic benefits from financial integration are better secured when countries achieve a number of "threshold conditions," including minimum levels of financial development and governance. Third, full financial integration requires the "trinity" of equality of access, rules, and treatment. Policymakers have to eliminate entry barriers, and once foreign institutions enter domestic markets, refrain from discriminating against them. In addition, policymakers must harmonize regulations further and build capacity, especially in banking supervision. Fourth, improving the "plumbing" of financial integration—financial infrastructure—by reducing transaction costs, can provide quick gains. Innovation in mobile payments can help reduce such costs, and regulators need to balance the associated benefits and risks.
Keywords: F36; F38; F65; G21; G28; 330